Clinical Nurse Specialist Practice Strategies for Children With Medical Complexity. Issue 1 (January 2021) - Murphy, Stephanie; Ehritz, Carly
Abstract : Purpose: Clinical nurse specialists are advanced practice nurses that influence patient care and nursing clinical practice through expert consultation and ongoing support. They play a vital role in caring for children with medical complexity. The purpose of this project is to highlight the practice of the clinical nurse specialist in identifying complex patient care needs and describe the resources needed to successfully transition a patient through the continuum of care by using a case example of a neonate with epidermolysis bullosa. Description of the Project: Caring for children with medical complexity can be challenging for healthcare providers and overwhelming for families once they are ready for discharge. Patient outcomes rely heavily on a specific and detailed plan of care, multidisciplinary collaboration, provider education, and safe transitions. The clinical nurse specialist can greatly influence these 4 components and positively impact outcomes for this patient population. Outcome: A patient with complex medical needs was successfully transferred from the intensive care unit to a medical floor and eventually discharged home. Conclusion: This framework can be used for any child with medical complexity as they transition across care settings to ensure safe and effective care is consistently provided. Abstract : Supplemental digital content is available in the text.